The dry season intensity as a key driver of NPP trends. Issue 6 (31st March 2016) - Murray‐Tortarolo, Guillermo; Friedlingstein, Pierre; Sitch, Stephen; Seneviratne, Sonia I.; Fletcher, Imogen; Mueller, Brigitte; Greve, Peter; Anav, Alessandro; Liu, Yi; Ahlström, Anders; Huntingford, Chris; Levis, Sam; et al.
Abstract: We analyze the impacts of changing dry season length and intensity on vegetation productivity and biomass. Our results show a wetness asymmetry in dry ecosystems, with dry seasons becoming drier and wet seasons becoming wetter, likely caused by climate change. The increasingly intense dry seasons were consistently correlated with a decreasing trend in net primary productivity (NPP) and biomass from different products and could potentially mean a reduction of 10–13% in NPP by 2100. We found that annual NPP in dry ecosystems is particularly sensitive to the intensity of the dry season, whereas an increase in precipitation during the wet season has a smaller effect. We conclude that changes in water availability over the dry season affect vegetation throughout the whole year, driving changes in regional NPP. Moreover, these results suggest that usage of seasonal water fluxes is necessary to improve our understanding of the link between water availability and the land carbon cycle. Key Points: We show that the dry season has become more intense over the arid regions in recent decades We find a linear relationship between such increased intensity and a decrease in NPP. The trend is predicted to continue over the future, reducing global NPP between 10 and 13% by 2100